Cord blood T regulatory cells synergize with ruxolitinib to improve GVHD outcomes - Ke Zeng; Hongbing Ma; Meixian Huang; Mi-Ae Lyu; Tara Sadeghi; Christopher R. Flowers; Simrit Parmar (Frontiers in Transplantation)
BackgroundAdoptive therapy with umbilical cord blood (UCB) T-regulatory (Treg) cells can prevent graft vs. host disease (GVHD). We hypothesize that UCB Tregs can treat GVHD and synergize with ruxolitinib, Jak2 inhibitor, to improve outcomes.MethodsUCB Treg potency and efficacy was examined using cell suppression assay and xenogeneic GVHD model, respectively. Ruxolitinib was fed continuously in presence or absence of CellTraceViolet tagged UCB Tregs on days +4, +7, +11, +18. Mice were followed for survival, GVHD score, hematology parameters and inflammation.ResultsAddition of ruxolitinib to UCB Tregs exerted synergistic suppressor function in vitro and improved persistence of UCB Tregs in vivo. Lower GVHD score, improved survival, increased hemoglobin level and platelet count, decreased inflammatory cytokines and decrease in CD3+ T cell lung infiltrate was observed in UCB Tregs+ruxolitinib recipients.ConclusionUCB Treg+Ruxolitinib combination improves outcomes in xenogeneic GVHD and should be explored in a clinical setting.